PENGARUH CSR DISCLOSURE DAN CAPITAL STRUCTURE TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING DI PERUSAHAAN-PERUSAHAAN MANUFAKTUR YANG LISTING DI BEI TAHUN 2011-2015 - Sri Wahyuni; Edyanus Herman Halim; Rendra Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of CSR disclosure and capital structure on firm value with financial performance as intervening variable. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange (BEI). The ecosystem variable in this research is capital structure and CSR Disclosure, while intervening variable is financial performance and dependent variable is firm value. This study has a population of 137 companies in manufacturing companies listed on the Indonesia Stock Exchange period 2011- 2015. This research uses purposive sampling technique and sample which fulfill as many as 44 companies. The method of data processing using multiple regression analysis and regression of moderation. SPSS software version 21.00. The results showed that CSR disclosure variable has a direct influence on financial performance. CSR disclosures have a direct influence on corporate value. Capital structures have a direct influence on financial performance. Capital structure has a direct influence on company value. Corporate value has a direct influence on financial performance. CSR disclosure has a direct influence on the value of a company mediated by financial performance. Capital structure has a direct influence on firm value mediated by financial performance.Keywords: CSR disclosure, capital structure, corporate value, financial performance